Analisis Waktu Baku dengan Metode Work Sampling untuk Menentukan Jumlah Tenaga Kerja di Bagian Pengepakan PT. Panganmas Inti Persada Cilacap - Pratiwi, Yuliyanti Dian; Hidayati, Nurul; Wahyudiantoro, Andi; Prasetyo, Nuniek Chandraswati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. Panganmas Inti Persada is a company that processes wheat grains into wheat flour. In the packaging section of this company, there is a problem, namely the lack of workers, so the purpose of this study is to determine the most optimal number of workers. This study uses the Work Sampling method by observing operator activities and calculating productive time. The results obtained in this study are the average productive time of all operators is 91.50% and idle time is 8.50%. The standard time to complete the product filling is 0.153 minutes and sewing is 0.152 minutes. While the number of workers needed for product filling is 1.26 people and sewing is 1.25 people. So the number of workers needed to complete the packaging work is 2.51 people or 3 people.